Maupassant : Practical Exercises. - Greimas, Algirdas Julien (John Benjamins Publishing Company, 1988)
Translated by Paul PerronMaupassant's short story, "Two Friends", is examined in order to test methodological tools and to hone them for their application in the analysis of narrative discourse, starting from the oral tale (Propp) and ending with the written tale instituted as literary genre. Complex procedures of textual production are identified: among which entire sequences as well as the "evenemential" level of narrative fade away in favor of its cognitive dimension. This semiotic investigation is accompanied by a challenge to certain conventions of literary criticism: dialogue, the locus.